2004
DOI: 10.1080/13607860412331303801
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cognitive impairment, functional impairment and care setting on dementia care mapping results

Abstract: Quality of life (QOL) for people with dementia has become a major focus over the past decade. Dementia care mapping (DCM) is an observational measure of quality of care given by staff in formal care settings, as well as a measure of QOL that has been used in many studies of people with dementia in residential care settings. However, the method itself has not been rigorously studied in a scientific manner. For this report, mapping data were collected for 166 persons with dementia in three types of care settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
4
12
0
1
Order By: Relevance
“…As shown in Table 3, higher WIB scores are associated with being more cognitively intact, non-agitated, non-depressed, and socially engaged, relationships that have been reported previously (Brooker et al, 1998;Chung, 2004;Edelman et al, 2004;Kuhn et al, 2004;Thornton et al, 2004). However, such a relationship is not unique to DCM, but is characteristic of many QOL measures (Sloane et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…As shown in Table 3, higher WIB scores are associated with being more cognitively intact, non-agitated, non-depressed, and socially engaged, relationships that have been reported previously (Brooker et al, 1998;Chung, 2004;Edelman et al, 2004;Kuhn et al, 2004;Thornton et al, 2004). However, such a relationship is not unique to DCM, but is characteristic of many QOL measures (Sloane et al, 2005).…”
Section: Discussionsupporting
confidence: 60%
“…Relationships were identified between dependency and well-being (WIB scores) and behaviours with the potential to lead to greater well-being (PPE scores). This supports the majority of previous research indicating that those patients with greater dependency were observed to have lower well-being using Dementia Care Mapping (Edelman et al, 2004). Cognitive impairment was identified as being a predictor of well-being and of potential for positive engagement.…”
Section: Discussionsupporting
confidence: 86%
“…Some DCM research has looked at the effect of cognitive impairment on PCC and well-being, albeit in people with dementia. Much of this evidence is equivocal with Edelman, Kuhn, and Fulton (2004) finding those with greater cognitive impairment displaying lower well-being, while other researchers report no significant relationship between cognitive impairment and well-being or activity as measured by DCM (Gigliotti, Jarrott, & Yorgason, 2004;Jarrot & Bruno, 2003). Research in this area relies on measuring cognitive impairment accurately, with most studies using the Mini-Mental State Examination (MMSE: Folstein, Folstein, & McHugh, 1975) as the primary, or only measure of cognitive impairment.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ein guter Überblick dazu findet sich aber bei Ettema et al [5]. [75], aber fehlende oder schwache Korrelationen nicht als Einschränkung der externen Validität interpretiert werden, sondern nur als Hinweis darauf, dass das Instrument mehr misst als nur Kognition [3]. Bislang gibt es zwar keine verbindlichen Richtlinien für LQ−Mes− sungen bei Demenzkranken, aber die meisten Autoren stimmen darin überein, dass Patienten mit leichter bis mittelschwerer De− menz ihre Lebensqualität selbst valide und reliabel beurteilen können [7 ± 9,15, 36, 72].…”
Section: Generische Instrumente Zur Lebensqualitätsbeurteilungunclassified